Qaraqalpaq ádebiyatında poemanıń janrlıq hám formalıq ózgesheligi (SCIENCE and SOCIETY, 2021)
The article examines the literary genre, type, genre and genre form of poem in Karakalpak literary criticism. And also given the au-